IgG4 autoantibodies are inhibitory in the autoimmune disease bullous pemphigoid. (September 2016) - Zuo, Yagang; Evangelista, Flor; Culton, Donna; Guilabert, Antonio; Lin, Lin; Li, Ning; Diaz, Luis; Liu, Zhi
Abstract: The IgG4 subclass of antibodies exhibits unique characteristics that suggest it may function in an immunoregulatory capacity. The inhibitory function of IgG4 has been well documented in allergic disease by the demonstration of IgG4 blocking antibodies, but similar functions have not been explored in autoimmune disease. Bullous pemphigoid (BP) is a subepidermal autoimmune blistering disease characterized by autoantibodies directed against BP180 and an inflammatory infiltrate including eosinophils and neutrophils. Animal models have revealed that the NC16A region within BP180 harbors the critical epitopes necessary for autoantibody mediated disease induction. BP180 NC16A-specific IgG belong to the IgG1, IgG3, and IgG4 subclasses. The purpose of this study was to determine effector functions of different IgG subclasses of NC16A-specific autoantibodies in BP. We find that IgG4 anti-NC16A autoantibodies inhibit the binding of IgG1 and IgG3 autoantibodies to the NC16A region. Moreover, IgG4 anti-NC16A blocks IgG1 and IgG3 induced complement fixation, neutrophil infiltration, and blister formation clinically and histologically in a dose-dependent manner following passive transfer to humanized BP180-NC16A mice. These findings highlight the inhibitory role of IgG4 in autoimmune disease and have important implications for the treatment of BP as well as other antibody mediated inflammatory and autoimmune diseases. Highlights: Autoantibodies in bullous pemphigoid belong to the IgG1, IgG3, and IgG4 subclasses. Patient derived antigen specific IgG1/3 induce disease in vivo . Patient derived antigen specific IgG4 inhibits IgG1/3 induced disease in vivo . Inhibitory IgG4 may be useful for treating bullous pemphigoid.